The Function and Meaning of Tope’ le’leng in the Death Ritual of The Kajang Tribe, South Sulawesi - Ninik Juniati (Jurnal Kawistara, 2022)
Tope’ le’leng in the Kajang language means black sarong and is a typical sarong of the Kajang tribe worn by men and women, both for daily wear and worn at various ceremonies held by this tribe. The study of tope’ le’leng has been quite a lot. Still, no one has discussed its function and meaning in the death ritual of the Kajang tribe, considering that tope’ le’leng has been recognized as one of the Kajang tribe’s identities among other tribes in Indonesia. This study examines the function and meaning of Tope’ le’leng in death rituals, starting from when the corpse was still at home, funeral preparation, funeral processions, and follow-up rituals until 100 days. This research used an ethnographic approach with descriptive analysis. Data analysis used triple pattern (Pola Tiga) theories in Paradoxical Aesthetics from Jakob Sumardjo. The data sources in this study are Tope’ le’leng, the funeral ritual itself, the shaman who led the death rituals, and the local community who followed the funeral ritual. Data collection techniques used participatory observation and interviews. The results showed that Tope’ le’leng functioned as an object of donation, a sign of grief. It is a marker of a family of mourning (not wearing clothes other than tope’ le’leng) as a ritual object to cover the bamboo coffin and Pammorangan. Tope’ le’leng, as a ritual object, shows the social strata or economic level of the grieving family in the community. The Kajang people believed that the deceased spirit could see the family and the shaman as long as they did not wear clothes other than tope’ le’leng for 100 days. As one of the ritual and sacred objects, tope’ le’leng has presented a moment of transcendence and belief in the existence of spirits in death rituals. Based on the triple pattern theory (Pola Tiga), namely the relationship between the upper, middle, and lower worlds. Tope’ le’leng has another function as a relationship connector between God, man, and nature.  The simplicity of its form and composition does not detract from its function and meaning and even reinforces its sacredness as a ritual object in patuntung beliefs.